CAR-T cell development for Cutaneous T cell Lymphoma: current limitations and potential treatment strategies - To, Van; Evtimov, Vera J.; Jenkin, Graham; Pupovac, Aleta; Trounson, Alan O.; Boyd, Richard L. (Frontiers in Immunology, 2022)
Chimeric antigen receptor (CAR)-T therapy has demonstrated remarkable outcomes for B cell malignancies, however, its application for T cell lymphoma, particularly cutaneous T cell lymphoma (CTCL), has been limited. Barriers to effective CAR-T cell therapy in treating CTCL include T cell aplasia in autologous transplants, CAR-T product contamination with leukemic T cells, CAR-T fratricide (when the target antigen is present on normal T cells), and tumor heterogeneity. To address these critical challenges, innovative CAR engineering by targeting multiple antigens to strike a balance between efficacy and safety of the therapy is necessary. In this review, we discuss the current obstacles to CAR-T cell therapy and highlight potential targets in treating CTCL. Looking forward, we propose strategies to develop more powerful dual CARs that are advancing towards the clinic in CTCL therapy.